Communication—Excellent Threshold Selector Characteristics of Cu2S-Based Atomic Switch Device. (1st January 2017) - Lim, Seokjae; Woo, Jiyong; Hwang, Hyunsang
Abstract : Bipolar-threshold switching was demonstrated using volatile-atomic switches (VAS) for cross-point selector applications. The VAS (Cu/Cu2 S/W) exhibits asymmetric current–voltage (I–V) characteristics. An abrupt conductance change occurs by the formation of a Cu filament when a positive voltage is applied to the Cu electrode. Meanwhile, nonlinear I–V characteristics are observed because of the high concentration of vacancy of Cu under a negative voltage. We thus introduce the complementary-VAS configuration for the self-compliance characteristics at both polarities. Furthermore, the increased the switching voltage at a fast sweeping rate allows the VAS to show a strong immunity to electrical disturbance.